Investigação dos efeitos genotóxicos, citotóxicos e citostáticos dos antifúngicos fluconazol e terbinafina em células de eucarioto - Tolomeotti, Danielle (2012)
Fluconazole is a drug of broad spectrum, effective against a variety of pathogenic fungi. Terbinafine is an antifungal that has demonstrated activity against most of the superficial fungal infections. The present study investigated the genotoxic effects of fluconazole and terbinafine on the induction of chromosomal aberrations (CA), micronuclei (MN), nucleoplasmic bridges, nuclear buds (NB) and sister chromatid exchanges (SCE), in vitro. The cytotoxic and cytostatic effects of the compounds were investigated through the analysis of the following indices: mitotic (MI), replication (RI), nuclear division (NDI) and cytokinesis-block proliferation (CBPI). The concentrations of fluconazole tested were 6.7, 12.5, 25, 50 and 100 ?g mL-1 and of terbinafine 1, 5, 25, 50 and 100 ?g mL-1. In all assays the mitomycin C was used as a positive control and 2% DMSO as a negative control. Statistical analyses of data were performed using the Kruskal-Wallis test, at 5% significance. No statistically significant difference between the concentrations of fluconazole tested and negative control, in the average count of cells with: CA (CCA), MN (CMN), NB (CNB) and mean counts per cell of SCE (SCE/cell) was found. There was also no statistically difference between the concentrations of fluconazole tested and negative control, in the average values of: MI, NDI, CBPI and RI. Increase in dose dependent manner, was not observed between the concentrations of fluconazole tested, in relation to CCA, CMN, CNB and the average score of SCE/cell. For the terbinafine no statistically significant difference between the concentrations tested and negative control, in the average count of CCA, CMN, CNB and mean counts SCE/cell was found. There was also no statistical difference between the concentrations of tested terbinafine and negative control, for the average values of: for MI, NDI, CBPI e RI. There was no increase in dose dependent manner, between the terbinafine concentrations tested in relation to CCA, CNB and the average score of SCE/cell. Terbinafine caused an increase in dose dependent manner in CMN. It is concluded that terbinafine and fluconazole, in the concentrations tested, have no genotoxic, cytotoxic or cytostatic effects.